2019
DOI: 10.1590/s1677-5538.ibju.2019.0058
|View full text |Cite
|
Sign up to set email alerts
|

The association between CHA2DS2-VASc score and erectile dysfunction: a cross-sectional study

Abstract: Purpose: This study aims to assess the association between CHA 2 DS 2-VASc score and erectile dysfunction in patients who were admitted to cardiology outpatient clinics. Materials and methods: One hundred and two male patients who were admitted to the cardiology outpatient clinic were included to the study. Erectile dysfunction was evaluated in the urology outpatient clinic in the same hospital and scored using Turkish Version of The International Index of Erectile Function. CHA 2 DS 2-VASc score was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…According to Apostolo et al ( 26 ), 69.3% of heart failure patients had ED. In Turkey, Karabulut et al ( 27 ) found that patients with heart failure had lower IIEF-5 scores than their counterpart without heart failure. This phenomenon was also replicated in rat models.…”
Section: Discussionmentioning
confidence: 99%
“…According to Apostolo et al ( 26 ), 69.3% of heart failure patients had ED. In Turkey, Karabulut et al ( 27 ) found that patients with heart failure had lower IIEF-5 scores than their counterpart without heart failure. This phenomenon was also replicated in rat models.…”
Section: Discussionmentioning
confidence: 99%